Plant breeding : (Blackwell Pub., 2006)
Plant breeding practices have improved the livelihoods of millions. Current breeding practices have allowed farmers to produce enough crops to feed growing populations, added significant profits in the grain trade, and minimized the amount of land needed for agricultural production by permitting more intensive use of existing crop lands. This volume reviews the status of the major challenges, approaches, and accomplishments of plant breeding programs from around the world.